Pengaruh Senam Kaki terhadap Kadar Glukosa Darah dan Nilai ABI Penderita DM - Trisna, Efa; Musiana, Musiana (Politeknik Kesehatan Tanjungkarang, 2018)
Riskesdas (2013), reported the prevalence of Diabetes Mellitus (DM) in Indonesia based on interviews showed an increase from 1.1 percent (2007) to 2.1 percent in 2013. The International Diabetes Federation (IDF) estimates that DM patients in Indonesia in 2020 amount to 178 million people above 20 years and assuming DM prevalence of 4.6% will be obtained 8.2 million DM patients. Lampung Provincial Health Office Data (2015), DM patients in Lampung Province in 2015 totaled 26,791 people. This number increased compared to 2014 totaling 24,238 people, and in 2013 which amounted to 23,783 people. One of the most common complications of diabetes mellitus is a diabetic foot (diabetic foot), which can manifest as ulcer, infection, and gangrene and Charcot arthropathy. This study was to determine the effect of foot gymnastics on blood glucose levels and ABI values of DM patients. The research design was quasy-experimental with pre and post-test group design data collection. The number of respondents was 80 respondents consisting of 40 groups intervention and 40 control groups. Data were analyzed using T-test. The results were 0.008; 0.002; 0,000; and 0,000. There was a difference between blood glucose levels before and after the intervention. Suggestion for DM sufferers to be able to do foot exercises regularly 3 times a week to prevent blood control and prevent blood circulation disorders.